TALC DEPOSITS OF JURAGH AREA, DISTRICT SWAT~PAKISTAN (Biological Sciences - PJSIR, 2022)
Good quality talc occur in the Juragh area of district Swat. The deposits lie in the western part of the suture (LesserHimalayas, exposed in Pakistan) of the Indo-Pak plate in tectonic interaction with Eurasia in the north. The deposit iscomprised of talc and antigorite while the country rocks are quartz-mica and dolomitic schists. The talc may have beendeveloped by secondary processes undertaken by the action of hydrothermal solutions on metamorphosed calcareoussediments and impure marbles as well as retrogression during the Himalayan orogeny. The talc is suitable for utilizationin a range of industries.